Real-Time Imaging of Aneurysmal Rupture Causing an Isolated Acute Subdural Hematoma. (1st March 2022) - Hong, Christopher; Renedo, Daniela; Sujijantarat, Nanthiya; Koo, Andrew; Falcone, Guido J.; Malhotra, Ajay; Petersen, Nils H.; Matouk, Charles
Abstract : A 51-year-old woman with hypertension presented with a 3-week history of progressive right cranial nerve III palsy and headache. During emergency department evaluation, while in the MRI scanner, she became acutely unresponsive. MRI captured a rapidly expanding acute subdural hematoma (aSDH) (Figure). She was taken for emergent decompressive craniectomy. Postoperative imaging demonstrated a ruptured right-sided posterior communicating artery aneurysm.